Uneven Recovery from the COVID-19 Pandemic: Post-lockdown Human Mobility Across Chinese Cities - Yanyan Liu; Shuang Ma; Ren Mu (Institute of Labor Economics (IZA), 2021)
How quickly can we expect human mobility to resume to pre-pandemic levels after lockdowns? Does pandemic severity affect the speed of post-lockdown recovery? Using real-time cross-city human mobility data from China and a difference-in-difference-in-differences framework, we find that mobility in most cities resumed to normal six weeks after reopening. In contrast, the epicenter cities, those with the worst outbreaks, were slow to recover; twelve weeks after reopening, mobility had not returned to the pre-pandemic levels. We provide suggestive evidence that relatively undiminished pandemic concerns may have slowed down mobility recovery in the epicenter region. Our findings imply that a severe pandemic experience impedes post-lockdown mobility recovery. From a policy perspective, this study suggests that it is important to successfully contain the pandemic to achieve a faster post-lockdown recovery.
Keywords: L60; H12; I18; 330; COVID-19; population mobility; post-lockdown; China